2012
DOI: 10.4104/pcrj.2011.00098
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between self-report and medical records on signs and symptoms of respiratory illness

Abstract: Background: Information on patient symptoms can be obtained by patient self-report or medical records review. Both methods have limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 57 publications
5
29
1
Order By: Relevance
“…Sikorskii et al cancer symptoms [28]; Barbara et al respiratory illness [29]), we did not find any reports on the concordance between patient (parent) report of Education or Tobacco and EMR documentation. Several studies have found EMR implementation to increase screening for smoking [30][31][32], but the extent to which Tobacco exposure is captured by EMR is not strongly reflected in the literature, as we only found one study addressing this relationship [18].…”
Section: Introductioncontrasting
confidence: 56%
“…Sikorskii et al cancer symptoms [28]; Barbara et al respiratory illness [29]), we did not find any reports on the concordance between patient (parent) report of Education or Tobacco and EMR documentation. Several studies have found EMR implementation to increase screening for smoking [30][31][32], but the extent to which Tobacco exposure is captured by EMR is not strongly reflected in the literature, as we only found one study addressing this relationship [18].…”
Section: Introductioncontrasting
confidence: 56%
“…Direct reporting from patients is helpful in understanding their detailed symptoms and the impacts on quality of life, which medical professionals tend to overlook [1][2][3]. As an example, content analysis of comments posted by patients' online communities revealed unknown long-term antidepressant withdrawal symptoms [4] In addition, attempts have been made to detect adverse drug reaction signals from patients' posts on social media [5][6].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…In this issue of the PCRJ, Barbara and colleagues 1 report the agreement between patient-recorded and clinician-recorded symptoms of respiratory illness. Contrary to other research, the study revealed that the patients recorded fewer symptoms than were captured by the clinicians following consultation.…”
mentioning
confidence: 99%
“…There are two important implications of this study; 1 • Firstly, policy makers should be mindful of the impact that public health decisions (e.g. cutting costs) can have upon a patient's perceived risk of not receiving an appropriate level of treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation